Place de la langue première et des approches plurielles dans les manuels de FLE du niveau secondaire en Pologne - Chmiel-Bożek, Halina (Neofilolog, 2023)
The Council of Europe has been promoting pluralistic approaches for more than 20 years, considering them as an effective tool for the development of plurilingual competence, regarded as indispensable in multilingual Europe. The aim of the article is to determine the place of the first language and pluralistic approaches in the latest (published after 2018) French textbooks for high schools. The analysis shows that elements characteristic of pluralistic approaches are present in varying degrees in the textbooks analysed, both at the textual and paratextual level. Textbook authors use pluralistic approaches in a variety of ways, for example by referencing the knowledge of Polish, English as well as non-verbal language.